Produk-Produk Dana Pihak Ketiga (DPK) Sebagai Sarana Simpanan Dana Dan Layanan Pendukung Di PT Bank Sumut KCP Syariah Simpang Kayu Besar - Azhari, Alwan; Dalimunthe, Ahmad Amin (Yayasan Rahmat Islamiyah, 2024)
The banking system in Indonesia is currently growing rapidly, which aims to facilitate the banking sector and especially from the convenience and security of the banking customers themselves. This study aims to find out what are the products of third party funds as a means of depositing funds and supporting services at Bank Sumut Syariah Kcp Simpang Kayu Besar. In this study, the authors used qualitative research methods with descriptive analysis techniques. Then all the sources of this research were obtained by conducting interview sessions with the bank, while the secondary data obtained in this study were obtained based on what had been obtained from the literature study. In the process of raising funds, the bank has several ways of raising funds and one of them is by relying on Third Party Funds (DPK). In this DPK, the Bank offers several products for depositing funds, namely Savings, Current Accounts, and Time Deposits. Based on data obtained from PT Bank Sumut Syariah Kcp Simpang Kayu Besar, there is a decrease and increase in the annual margin that occurs in TPF in 2019-2021 at PT Bank Sumut Syariah Simpang Kayu Besar.